Beyond the Text: Comparative Analysis of Paratextual Elements in the Arabic Translations of Toni Morrison’s Paradise - Chirig, Abdelkrim; Bouziane, Karima; Zakhir, Marouane (International Journal of Language and Literary Studies, 2024)
This study investigates the paratextual elements in the Arabic translations of Toni Morrison’s Paradise, focusing on the translations by Tawfiq Al-Asadi and Ali Basha. Paratextual elements, including introductions, book covers, titles, forewords, and footnotes, play a crucial role in shaping reader reception and interpretation, particularly in translated literary works. This study aims to analyze how these elements influence the reception and interpretation of the novel within the Arabic-speaking world. Through a comparison of the visual and semantic interfaces between the source text (ST) and the target texts (TTs), this research reveals how paratextual elements are adapted or transformed to suit the cultural context of the target audience. The analysis encompasses book covers, title translations, forewords, dedications, and footnotes, highlighting the impact of these elements on reader engagement and understanding. The findings suggest that the translators’ choices reflect their cultural, ideological, and gendered perspectives, influencing their interpretative strategies and the final reception of the translated text. These paratextual elements highlight literary translation's obstacles and translators' active participation in crossing cultural and linguistic boundaries.